A transparent polyurethane hot melt adhesive and a method for preparing the same
Patent Information
- Application Number
- CN202411679637.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-11-22
AI Technical Summary
[0004]为了解决现有技术PET废弃物无法高值化回收利用以及传统聚氨酯热熔胶过度依赖石化资源的问题,本发明提出了一种透明聚氨酯热熔胶及其制备方法
1.PET废弃物的高值化回收:本发明制备透明聚氨酯热熔胶的原料包括废弃PET片、聚(碳酸酯-醚)二元醇等,其中聚(碳酸酯-醚)二元醇的组分为PET醇解产物,最大化实现了对PET废弃物的回收利用,减少了对石化资源的严重消耗。同时利用PET的刚性、极性和透明性等特性,显著提升了透明聚氨酯热熔胶的透明性、粘附性和机械性能,不仅有效解决了PET废弃物的处理问题,实现了塑料资源的高值化利用,也为塑料回收行业的可持续发展提供了新的思路。
Smart Images

Figure CN119463780B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polyurethane hot melt adhesive technology, specifically to a transparent polyurethane hot melt adhesive and its preparation method. Background Technology
[0002] Polyethylene terephthalate (PET) is one of the most widely used synthetic resins today, applied in beverage bottles, food packaging, textiles, and electronic device housings. Due to its excellent mechanical properties, heat resistance, and chemical stability, PET plays a vital role in industrial production. However, with the large-scale production and use of PET, the resulting environmental problems have become increasingly severe. As a non-biodegradable plastic material, the accumulation and disposal of PET waste places enormous pressure on the environment. Data shows that in 2018, the global annual production of PET reached 79.68 million tons, generating tens of millions of tons of waste. However, data from 2023 indicates that its recycling rate was only 6.5 million tons, accounting for 32%. Traditional methods for treating PET waste include landfill, incineration, and physical degradation recycling technologies. However, due to PET's unique aromatic ring structure, it is difficult to degrade in nature. PET waste takes hundreds of years to decompose in nature, meaning it will persist in the ecological environment for a long time, affecting the quality of soil, water, and air. At the same time, the incineration of PET plastics releases toxic gases, further exacerbating air pollution and threatening human health. Furthermore, physical degradation recycling technology cannot achieve high-value recycling of waste PET; even if the depolymerization method is used to prepare monomers to recycle PET waste, it is an efficient chemical recycling method, but its complex post-processing will increase the recycling cost.
[0003] Polyurethane hot melt adhesives are important adhesives with excellent bonding properties, low-temperature resistance, and shear strength, making them promising for PET recycling and reuse. However, the synthesis of polyurethane hot melt adhesives heavily relies on petrochemical resources, typically prepared from petroleum-based polymer diols and diisocyanates. This process releases greenhouse gases, increases carbon emissions, and negatively impacts the environment, leading to unsustainable development challenges for the industry itself. Therefore, to address the issues of the inability to recycle PET waste at high value and the over-reliance of traditional polyurethane hot melt adhesives on petrochemical resources, developing a novel PET-based polyurethane hot melt adhesive material has become a current research hotspot, providing a greener and more efficient solution for the sustainable development of the plastics recycling industry. Summary of the Invention
[0004] To address the limitations of existing technologies in the high-value recycling of PET waste and the over-reliance of traditional polyurethane hot melt adhesives on petrochemical resources, this invention proposes a transparent polyurethane hot melt adhesive and its preparation method. The technical solution of this invention is as follows: A transparent polyurethane hot melt adhesive, formed by reacting components comprising the following parts by weight: 420-510 parts of waste PET sheets, 35-48 parts of sulfur-containing diols, 0.15-0.30 parts of antioxidants, 0.18-0.47 parts of catalyst I, 180-240 parts of poly(carbonate-ether) diols, 0.05-0.12 parts of catalyst II, and 115-142 parts of diisocyanate; The catalyst I is one or a combination of at least two of the following: tetrabutyl titanate, tetraisopropyl titanate, diethyl zinc, zinc octanoate, zinc acetate, manganese acetate, manganese phosphate, zinc phosphate, calcium phosphate, zinc oxide, and zinc chloride. Catalyst II is one or a combination of at least two of dibutyltin dilaurate, stannous octanoate, and bismuth neodecanoate. The sulfur-containing diol is one or a combination of at least two of the following: 3,7-dithia-1,9-nonanediol, 3,5-dithia-1,7-heptanediol, 2,2′-thiodiethanol, 3,6-dithia-1,8-octanediol, and 1,4-dithia-2,5-diol. The antioxidant is one or a combination of at least two of the following: triethyl phosphite, pentaerythritol diphosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, bisoctadecyl pentaerythritol diphosphite, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexamethylenediamine; The poly(carbonate-ether) diol was prepared according to the preparation method disclosed in Chinese Patent Document 201110231493.6; The diisocyanate is one or a combination of at least two of the following: isophorone diisocyanate, 1,6-hexane diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, diphenylmethane-4,4'-diisocyanate, 1,4-cyclohexane diisocyanate, tetramethyl isophthalimide diisocyanate, trimethyl-1,6-hexamethylene diisocyanate, 1,4-cyclohexane dimethyl diisocyanate, and norbornene diisocyanate; The poly(carbonate-ether) diol has a number average molecular weight Mn of 3300~6000 and a carbonate unit content CU of 30%~36%.
[0005] A method for preparing the above-mentioned transparent polyurethane hot melt adhesive includes the following steps: S1: Under nitrogen protection, waste PET sheets, sulfur-containing diol, catalyst I and antioxidant are sequentially added to the reactor for heating treatment. After reaching the temperature, the mixture is stirred to react and obtain the first intermediate. S2: The first intermediate, poly(carbonate-ether) diol, catalyst II and diisocyanate are added to the reactive screw, the heating temperature of each stage of the reactive screw is set, and after heating, the reactants are cut into particles underwater to obtain transparent polyurethane hot melt adhesive particles. Furthermore, the reactor in S1 is heated to 120~180℃; Furthermore, the reaction time in S1 is 0.5~2.5 h; Furthermore, the heating temperatures in each stage of S2 are 150℃, 180℃, 180℃, 190℃, 190℃, 180℃ and 140℃ respectively; Furthermore, the heating temperature stay time in each stage of S2 is 3~5 min.
[0006] Compared with existing technologies, this invention solves the problems of the inability to recycle PET waste at high value and the over-reliance of traditional polyurethane hot melt adhesives on petrochemical resources. Specifically, the beneficial effects are as follows: 1. High-value recycling of PET waste: The raw materials for preparing transparent polyurethane hot melt adhesive in this invention include waste PET sheets, poly(carbonate-ether) diol, etc., wherein the poly(carbonate-ether) diol is a PET alcoholysis product, maximizing the recycling of PET waste and reducing the severe consumption of petrochemical resources. Simultaneously, utilizing the rigidity, polarity, and transparency of PET, the transparency, adhesion, and mechanical properties of the transparent polyurethane hot melt adhesive are significantly improved. This not only effectively solves the problem of PET waste disposal and achieves high-value utilization of plastic resources, but also provides a new approach for the sustainable development of the plastic recycling industry.
[0007] 2. Reducing Over-Reliance on Petrochemical Resources: The preparation process of traditional polyurethane hot melt adhesives typically relies excessively on petrochemical raw materials, such as petroleum-based isocyanates and polyols. The transparent polyurethane hot melt adhesive provided by this invention uses waste PET sheets as the main raw material, and the poly(carbonate-ether) diol used is a PET alcoholysis product, effectively reducing over-reliance on petrochemical resources. This raw material substitution strategy not only helps reduce the consumption of non-renewable resources but also mitigates the environmental impact of PET waste to some extent. It also effectively reduces the production input cost of transparent polyurethane hot melt adhesives, which is of positive significance for improving the stability and sustainability of the industrial chain.
[0008] 3. High Transparency: The transparent polyurethane hot melt adhesive prepared by this invention has a light transmittance of 93.5%~98.3%, which is 50.8%~74.3% higher than similar products; the haze is 0.15%~0.26%, which is 1.7%~4.6% lower than similar products. This is because the waste PET sheet used as raw material itself has excellent transparency, and the amorphous structure of poly(carbonate-ether) diol can maintain its good transparency by reducing light scattering caused by crystallization. The use of both effectively enhances the transparency of the transparent polyurethane hot melt adhesive. At the same time, the introduction of heteroatom sulfur into the transparent polyurethane hot melt adhesive enhances the regulation of the dual soft segment structure of waste PET sheet and poly(carbonate-ether) diol by heteroatom sulfur and optimizes the compatibility between the two, thereby reducing the haze and light scattering of the material, and thus enhancing the transparency.
[0009] 4. Excellent glass adhesion: The peel strength of the transparent polyurethane hot melt adhesive prepared in this invention is 3.2~4.7 N / mm, which is 0.5~2.4 N / mm higher than similar products. This is due to the characteristic that the polar groups (such as carboxyl groups, carbonate groups, and ether groups) in the molecular structure of PET and poly(carbonate-ether) diol can physically adsorb and have a synergistic effect with the glass surface, thereby enhancing the adhesion of the transparent polyurethane hot melt adhesive. In addition, the amorphous structure of poly(carbonate-ether) diol and the presence of carbonate groups with high cohesive energy can enhance the tensile strength and elongation at break of the transparent polyurethane hot melt adhesive, further enhancing its adhesion to glass. Attached Figure Description
[0010] Figure 1 Infrared spectrum of the transparent polyurethane hot melt adhesive prepared in Example 1; Figure 2 A photograph of the transparent polyurethane hot melt adhesive particles prepared in Example 1; Figure 3 Photograph of the hot melt adhesive particles prepared for Comparative Example 1. Detailed Implementation
[0011] To make the technical solutions of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. It should be noted that the following embodiments are only used to better understand the technical solutions of the present invention and should not be construed as limiting the present invention.
[0012] The poly(carbonate-ether) diols used in the following examples were prepared according to the preparation method disclosed in Patent Document 201110231493.6, specifically the poly(carbonate-ether) diols corresponding to Examples 8, 12, 15 and 17 in the specification of that patent document.
[0013] Example 1. S1: Under nitrogen protection, 420 g of waste PET sheets, 35 g of 2,2′-thiodiethanol, 0.18 g of tetrabutyl titanate and 0.15 g of triethyl phosphite were sequentially added to the reactor. After the temperature was raised to 120°C, stirring was started and the reaction was carried out for 2.5 h to obtain the first intermediate. S2: The first intermediate, 180 g of poly(carbonate-ether) diol (Mn=3300, CU=30.6%), 0.05 g of dibutyltin dilaurate and 115 g of isophorone diisocyanate were added to a reactive screw. The heating temperatures of each stage of the reactive screw were 150℃, 180℃, 180℃, 190℃, 190℃, 180℃ and 140℃ respectively, and the heating time of each stage was 3 min. After the heating was completed, the product was cut into pellets underwater to obtain transparent polyurethane hot melt adhesive particles.
[0014] like Figure 1 Infrared spectrum of transparent polyurethane hot melt adhesive: 731.0 cm⁻¹ -1 795.6 cm -1 873.7 cm -1 944.1 cm -1 1017.4 cm -1 1046.3 cm -1 1104.2 cm -1 1121.5 cm -1 1170.7 cm -1 1272.1 cm -1 1378.1 cm -1 1408.9 cm -1 1455.2 cm -1 1505.3 cm -1 1580.6 cm -1 1616.3 cm -1 1721.4cm -1 1954.8 cm -1 2957.6 cm -1 3064.7 cm -1 3434.1 cm -1 As can be seen from the figure, 1721.4 cm - The strong absorption peak at ¹ corresponds to the stretching vibration of the carbonyl group (C=O), which is a key characteristic of polyurethane molecules; at 3434.1 cm⁻¹... - The broad peak at ¹ indicates significant intramolecular or intermolecular hydrogen bonding interactions in the transparent polyurethane hot melt adhesive, thus proving its internal soft segment structure; at 731.0 cm⁻¹ - ¹ and 1616.3 cm- The peak at ¹ reveals the presence of an aromatic ring in the isocyanate; meanwhile, the peaks at 1017.4–1121.5 cm⁻¹ also indicate this. - The peak at position ¹ represents the vibration of the COC bond, proving that the soft segment structure of the transparent polyurethane hot melt adhesive contains polyether groups. In summary, this transparent polyurethane hot melt adhesive possesses a typical polyurethane structure with microphase separation of soft and hard segments, endowing it with excellent adhesion, flexibility, and thermal stability. Figure 2 The image shows a photograph of the transparent polyurethane hot melt adhesive particles prepared in this embodiment. As can be seen from the image, the polyurethane hot melt adhesive is transparent.
[0015] Example 2. S1: Under nitrogen protection, 510 g of waste PET sheets, 48 g of 3,7-dithia-1,9-nonanediol, 0.47 g of tetraisopropyl titanate and 0.30 g of pentaerythritol diphosphite were sequentially added to the reactor. After the temperature was raised to 180℃, stirring was started and the reaction was carried out for 0.5 h to obtain the first intermediate. S2: The first intermediate, 240 g of poly(carbonate-ether) diol (Mn=6000, CU=34.3%), 0.12 g of stannous octoate and 142 g of 4,4'-dicyclohexylmethane diisocyanate were added to a reactive screw. The heating temperatures of each stage of the reactive screw were 150℃, 180℃, 180℃, 190℃, 190℃, 180℃ and 140℃ respectively, and the heating time of each stage was 5 min. After the heating was completed, the product was stretched and granulated underwater to obtain transparent polyurethane hot melt adhesive particles.
[0016] Example 3. S1: Under nitrogen protection, 460 g of waste PET sheets, 37 g of 3,5-dithia-1,7-heptanediol, 0.23 g of diethylzinc and 0.21 g of bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite were sequentially added to a reaction vessel. After the temperature was raised to 140°C, stirring was started, and the reaction was carried out for 1.5 h to obtain the first intermediate. S2: The first intermediate, 200 g of poly(carbonate-ether) diol (Mn=3500, CU=54.8%), 0.08 g of bismuth neodecanoate and 124 g of 1,6-hexamethylene diisocyanate were added to a reactive screw. The heating temperatures of each stage of the reactive screw were 150℃, 180℃, 180℃, 190℃, 190℃, 180℃ and 140℃ respectively, and the heating time of each stage was 4 min. After the heating was completed, the product was stretched and granulated underwater to obtain transparent polyurethane hot melt adhesive particles.
[0017] Example 4. S1: Under nitrogen protection, 480 g of waste PET sheets, 41 g of 3,6-dithia-1,8-octanediol, 0.32 g of zinc acetate and 0.22 g of dioctadecyl pentaerythritol diphosphite were sequentially added to the reactor. After the temperature was raised to 140°C, stirring was started and the reaction was carried out for 1 h to obtain the first intermediate. S2: The first intermediate, 225 g of poly(carbonate-ether) diol (Mn=3300, CU=30.6%), 0.1 g of stannous octoate and 130 g of 1,4-cyclohexane diisocyanate were added to a reactive screw. The heating temperatures of each stage of the reactive screw were 150℃, 180℃, 180℃, 190℃, 190℃, 180℃ and 140℃ respectively, and the heating time of each stage was 3 min. After the heating was completed, the product was stretched and granulated underwater to obtain transparent polyurethane hot melt adhesive particles.
[0018] Example 5. S1: Under nitrogen protection, 475 g of waste PET sheets, 42.5 g of 1,4-dithio-2,5-diol, 0.33 g of zinc phosphate and 0.18 g of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid] were sequentially added to a reaction vessel. After the temperature was raised to 145°C, stirring was started and the reaction was carried out for 2 h to obtain the first intermediate. S2: The first intermediate, 206 g of poly(carbonate-ether) diol (Mn=3500, CU=54.8%), 0.07 g of dibutyltin dilaurate and 128 g of tetramethylisophthalamide diisocyanate were added to a reactive screw. The heating temperatures of each stage of the reactive screw were 150℃, 180℃, 180℃, 190℃, 190℃, 180℃ and 140℃ respectively, and the heating time of each stage was 4 min. After the heating was completed, the product was stretched and granulated underwater to obtain transparent polyurethane hot melt adhesive particles.
[0019] Example 6. S1: Under nitrogen protection, 485 g of waste PET sheets, 45 g of 1,4-dithio-2,5-diol, 0.42 g of manganese acetate and 0.28 g of N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexamethylenediamine were sequentially added to a reaction vessel. After the temperature was raised to 165℃, stirring was started, and the reaction was carried out for 1.5 h to obtain the first intermediate. S2: The first intermediate, 215 g of poly(carbonate-ether) diol (Mn=5800, CU=35.2%), 0.08 g of bismuth neodecanoate and 135 g of 1,4-cyclohexanedimethyl diisocyanate were added to a reactive screw. The heating temperatures of each stage of the reactive screw were 150℃, 180℃, 180℃, 190℃, 190℃, 180℃ and 140℃ respectively, and the heating time of each stage was 5 min. After the heating was completed, the product was stretched and granulated underwater to obtain transparent polyurethane hot melt adhesive particles.
[0020] Comparative Example 1. 450 g of poly(carbonate-ether) diol (Mn=3300, CU=30.6%), 0.05 g of dibutyltin dilaurate, and 115 g of isophorone diisocyanate were added to a reactive screw compressor. The heating temperatures of each stage of the reactive screw compressor were 150℃, 180℃, 180℃, 190℃, 190℃, 180℃, and 140℃, respectively, with each stage lasting 3 minutes. After the heating was completed, the product was granulated underwater to obtain hot melt adhesive particles. Figure 3 The image shows a photograph of the hot melt adhesive particles prepared for this comparative example. It can be seen from the image that the hot melt adhesive particles have low transparency.
[0021] Comparative Example 2. 630 g of polypropylene glycol (Mn=2000), 0.05 g of dibutyltin dilaurate and 115 g of isophorone diisocyanate were added to a reactive screw. The heating temperatures of each stage of the reactive screw were 150℃, 180℃, 180℃, 190℃, 190℃, 180℃ and 140℃ respectively, and the heating time of each stage was 3 min. After the heating was completed, the product was stretched and granulated underwater to obtain hot melt adhesive particles.
[0022] Comparative Example 3. 630 g of polybutylene adipate (Mn=2000), 0.05 g of dibutyltin dilaurate, and 115 g of isophorone diisocyanate were added to a reactive screw. The heating temperatures of each stage of the reactive screw were 150℃, 180℃, 180℃, 190℃, 190℃, 180℃, and 140℃, respectively, with a heating time of 3 min for each stage. After the heating was completed, the product was stretched and granulated underwater to obtain hot melt adhesive particles.
[0023] Bonding process: After hot melt adhesive granules are pressed into sheets on a flat vulcanizing machine, they are placed between two pieces of glass and laminated together in a pattern of "3mm glass / 2mm hot melt adhesive / 3mm glass". The laminated sheets are then transferred to a vacuum oven, maintaining a vacuum level above 0.09 MPa. The oven temperature is uniformly increased from 25℃ to 150℃, held for 40 minutes, and then cooled to 40℃. The resulting laminated sample is then used for testing its adhesive properties.
[0024] The following table shows the performance parameters of the hot melt adhesives prepared in Examples 1-6 and Comparative Examples 1-3. The Shore A hardness of the hot melt adhesive was tested according to standard GB / T531-1999; tensile strength and elongation at break were tested according to standards GB / T528-1998 and GB / T528-1982, respectively, at a test temperature of 25°C, a test humidity of 55%, and a tensile testing machine loading speed of 100 mm / min; the bond strength after bonding to the substrate was tested according to standard GB / T2790-1995; and light transmittance and haze were tested according to standard GB / T2410-1980, at a test temperature of 25°C and a test humidity of 50%.
[0025]
[0026] As shown in Table 1, the transparent polyurethane hot melt adhesives prepared in Examples 1-6 exhibit high transparency and low haze. Their light transmittance is as high as 93.5-98.3%, which is 50.8-74.3% higher than similar products; the haze is 0.15-0.26%, which is 1.7-4.6% lower than similar products. This is because the waste PET sheets used as raw materials have excellent transparency, and the amorphous structure of poly(carbonate-ether) diol can maintain its good transparency by reducing light scattering caused by crystallization. The use of both effectively enhances the transparency of the polyurethane hot melt adhesive. Simultaneously, the introduction of heteroatom sulfur into the transparent polyurethane hot melt adhesive enhances the regulation of the dual soft segment structure of waste PET sheets and poly(carbonate-ether) diol by heteroatom sulfur and optimizes their compatibility, thereby reducing the haze and light scattering of the material and enhancing its transparency. Meanwhile, the transparent polyurethane hot melt adhesive has strong adhesion to glass, with a peel strength of 3.2~4.7 N / mm, which is 0.5~2.4 N / mm higher than similar products. This is due to the presence of high cohesive carbonate groups in the poly(carbonate-ether) diol structure, and the synergistic effect of the carbonate and ether groups in the structure, which enhances the tensile strength, elongation at break, and adhesion to glass of the transparent polyurethane hot melt adhesive.
[0027] Compared to Examples 1-6, the hot melt adhesive prepared in Comparative Example 1 showed varying degrees of decrease in transmittance, haze, and peel strength. This was mainly due to the lack of waste PET sheet components, which resulted in a lack of heteroatom sulfur to regulate the soft segments, leading to a decrease in transparency and haze. However, due to the presence of high-cohesive carbonate groups in the polyol structure, it still maintained a certain tensile strength and elongation at break. Furthermore, the synergistic effect between the carbonate and ether groups in the polyol structure provided some adhesion between the hot melt adhesive and the glass. Even though the peel strength decreased, it could still be maintained above 2 N / mm. Comparative Example 2 used amorphous polypropylene glycol as the soft segment, and the prepared hot melt adhesive also maintained a certain level of transparency and haze. However, due to the low cohesive energy of polypropylene glycol, the tensile strength decreased, and the adhesion to the glass weakened. Comparative Example 3 used crystalline polyester polyol as the soft segment, and the prepared hot melt adhesive showed a significant decrease in both transparency and haze. Moreover, it had no adhesion to the glass and could be directly peeled off.
[0028] Obviously, the above embodiments are merely examples to clearly illustrate the technical solutions of the present invention, and are not intended to limit the technical solutions. Those skilled in the art can make other variations or modifications based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations. However, obvious variations or modifications derived therefrom are still within the protection scope of this invention.
Claims
1. A transparent polyurethane hot melt adhesive, characterized in that, It is produced by reacting components comprising the following parts by mass: 420-510 parts of waste PET sheets, 35-48 parts of sulfur-containing diols, 0.15-0.30 parts of antioxidants, 0.18-0.47 parts of catalyst I, 180-240 parts of poly(carbonate-ether) diols, 0.05-0.12 parts of catalyst II, and 115-142 parts of diisocyanate; The catalyst I is one or a combination of at least two of the following: tetrabutyl titanate, tetraisopropyl titanate, diethyl zinc, zinc octanoate, zinc acetate, manganese acetate, manganese phosphate, zinc phosphate, calcium phosphate, zinc oxide, and zinc chloride. Catalyst II is one or a combination of at least two of dibutyltin dilaurate, stannous octanoate, and bismuth neodecanoate. The transparent polyurethane hot melt adhesive is prepared by the following steps: S1: Under nitrogen protection, waste PET sheets, sulfur-containing diol, catalyst I and antioxidant are sequentially added to the reactor for heating treatment. After reaching the temperature, the mixture is stirred to react and obtain the first intermediate. S2: The first intermediate, poly(carbonate-ether) diol, catalyst II and diisocyanate are added to the reactive screw, the heating temperature of each stage of the reactive screw is set, and after heating is completed, the reactants are cut into particles underwater to obtain transparent polyurethane hot melt adhesive particles.
2. The transparent polyurethane hot melt adhesive according to claim 1, characterized in that, The sulfur-containing diol is one or a combination of at least two of the following: 3,7-dithia-1,9-nonanediol, 3,5-dithia-1,7-heptanediol, 2,2′-thiodiethanol, 3,6-dithia-1,8-octanediol, and 1,4-dithia-2,5-diol.
3. The transparent polyurethane hot melt adhesive according to claim 1, characterized in that, The antioxidant is one or a combination of at least two of the following: triethyl phosphite, pentaerythritol diphosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, bis(octadecyl)pentaerythritol diphosphite, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexamethylenediamine.
4. The transparent polyurethane hot melt adhesive according to claim 1, characterized in that, The diisocyanate is one or a combination of at least two of the following: isophorone diisocyanate, 1,6-hexane diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, diphenylmethane-4,4'-diisocyanate, 1,4-cyclohexane diisocyanate, tetramethyl isophthalimide diisocyanate, trimethyl-1,6-hexamethylene diisocyanate, 1,4-cyclohexane dimethyl diisocyanate, and norbornene diisocyanate.
5. The transparent polyurethane hot melt adhesive according to claim 1, characterized in that, The poly(carbonate-ether) diol has a number average molecular weight Mn of 3300~6000 and a carbonate unit content CU of 30%~36%.
6. The transparent polyurethane hot melt adhesive according to claim 1, characterized in that, The reactor in S1 is heated to 120~180℃.
7. The transparent polyurethane hot melt adhesive according to claim 1, characterized in that, The reaction time in S1 is 0.5~2.5 h.
8. The transparent polyurethane hot melt adhesive according to claim 1, characterized in that, The heating temperatures in each stage of S2 are 150℃, 180℃, 180℃, 190℃, 190℃, 180℃ and 140℃ respectively.
9. The transparent polyurethane hot melt adhesive according to claim 1, characterized in that, The heating temperature in each stage of S2 is maintained for 3 to 5 minutes.
Citation Information
Patent Citations
Preparation method of poly(carbonic ester-ether) glycol and preparation method of catalyst thereof
CN102432857B
Preparation method of poly(carbonic ester-ether) glycol and preparation method of catalyst thereof
CN102432857A
Carbon dioxide based reaction type polyurethane hot melt adhesive and preparation method thereof
CN108384500A